To Steal the Past: Russia's War on Ukraine's Identity - Getka, Joanna (Social Sciences E-Books Online, Collection 2026., 2026)
When juxtaposed with the practice of aggressive action and the brutal reality of war, Russian ideas appear completely incomprehensible. For more than three hundred years, Russians have cultivated the myth of the community, brotherhood of blood, and the indissoluble bond of the brotherly East Slavic peoples, while only recently they have unleashed a bloody war against the Ukrainians, killing children and defenceless civilians, burning and destroying everything along the way, and threatening the "mother of all Ruthenian cities" - Kyiv. The Russian invasion is difficult to explain using the concepts of realism or political pragmatism. They are also completely useless for understanding the mentality of Russians. To this day, the majority of Russians do not accept the existence of separate Ukrainian and Belarusian identities, considering Ukrainians and Belarusians as subgroups of the Russian nation, and the Belarusian and Ukrainian languages as dialects of Russian. They tacitly accept the Kremlin's arguments about the need to defend the Russian-speaking inhabitants of Ukrainian lands against the "fascist coup of the Banderites" and to bring about the "denazification" of Ukraine. The aim of the present work is to analyse the causes of this state of affairs from a linguocultural perspective.